The Role Of Supportive Leader And Entrepreneurial Motivation In Fostering Entrepreneurial Spirit - Soputan, Grace Jenny; Wuryaningrat, Nikolas Fajar (SEAN Institute, 2024)
The entrepreneurial spirit, which encompasses creativity and innovation, is linked to competitiveness and is essential in higher education to encourage innovative teaching methods. This study investigates the relationship between leadership behaviour, entrepreneurial motivation, and entrepreneurial spirit among teaching and education staff at Universitas Negeri Manado. This research novelty examines the relationship between entrepreneurial spirit and efforts to develop innovative learning methods for educators and education personnel in the higher education sector, a topic that has been largely overlooked in previous research. The creative destruction (CD) theory underpins this research, which describes how innovation drives economic restructuring and growth. Leadership, especially supportive, and motivation, both intrinsic and extrinsic, are critical in nurturing entrepreneurial spirit. This study employed a quantitative survey methodology with 92 respondents from teaching and education staff at Universitas Negeri Manado. Data analysis indicated that supportive leadership and entrepreneurial motivation significantly encourage entrepreneurial spirit. The findings indicated that the supportive leader and motivational factors have a notable impact on innovation, which in turn can foster an entrepreneurial spirit. This study emphasises the necessity for higher education leaders to recognise their role in fostering entrepreneurial spirit to drive institutional advancement and efficiency.